2016
DOI: 10.1002/hed.24505
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the incidence of osteoradionecrosis with conventional radiotherapy and intensity‐modulated radiotherapy

Abstract: Modern techniques of radiotherapy are supposed to decrease the incidence of osteoradionecrosis of the mandible (ORNM). The purpose of this study was to compare the incidence of ORNM after intensity-modulated radiotherapy (IMRT) in comparison to conventional 3D conformal radiotherapy techniques (conventional RT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Current literature reports that 40% of ORN cases manifest within 36 months after RT with a peak around 18 months . In our cohort, the median ORN onset was 5 months after RT, and the bone most commonly affected was the mandible (20/21 patients).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Current literature reports that 40% of ORN cases manifest within 36 months after RT with a peak around 18 months . In our cohort, the median ORN onset was 5 months after RT, and the bone most commonly affected was the mandible (20/21 patients).…”
Section: Discussionmentioning
confidence: 64%
“…It is defined as any area >1 cm of exposed bone in a previously irradiated situs, which is persisting for at least 3 months and is not caused by tumour recurrence/persistence . Even with intensity‐modulated radiation therapy (IMRT), the overall incidence of ORN remains at approximately 10% . Treatment strategies for ORN include conservative strategies (antibiotics) and surgical methods .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, however, reported no reduction in ORN rates in oropharyngeal cancer patients after IMRT in comparison to conventional 3D conformal radiotherapy techniques. [4] Most single-institution series of oral/oropharyngeal cancer patients treated with radiotherapy demonstrate frank osteoradionecrosis rates of approximately 1–11% [510]. Consequently, as Thariat et al[11] assert, “this low incidence may indeed make the establishment of statistically relevant correlations between dose and ORN difficult.”…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported different dose correlates and various permutations of maximum and mean mandibular dose as usable constraints[6, 7, 13, 14]. Traditionally, doses under 50 Gy were considered unlikely to contribute substantively to osteoradionecrosis, and most recommendations and clinical protocols restrict dose only above 50 Gy or more[510]. …”
Section: Introductionmentioning
confidence: 99%
“…Several reports have indicated the trend in the rate of jawrelated complications among patients receiving IMRT compared with those receiving 3-dimensional conformal RT (3D-CRT) [11,15,20]. In contrast, no reductions were observed in long-term ORNJ rates following IMRT in the absence of attempts to reduce the jaw volumes receiving high doses in IMRT plan optimization [21]. Thus, it is necessary to determine the dose-volumetric threshold of the jaw for IMRT plan optimization to reduce the incident of ORNJ.…”
Section: Introductionmentioning
confidence: 99%